Corporate Sustainability and Corporate Value - Wang, Ziqi (Transactions on Economics, Business and Management Research, 2024)
In recent years, the concept of sustainable development has gradually lodged itself in the public mind, and there is increasing emphasis on companies’ performance in environmental, social, and corporate governance (ESG) aspects. This paper empirically investigates the impact of corporate ESG performance on firm value based on all A-share listed companies in China from the first quarter of 2015 to the fourth quarter of 2020 as the initial research sample. The research results indicate that the better the corporate ESG performance, the higher the firm value. The study provides clear insights: firstly, ESG performance can enhance firm value, revealing that ESG can reduce information asymmetry and reduce financial risks for enterprises. Secondly, ESG performance is an endogenous driving force for companies to promote environmental protection, social responsibility, and corporate governance construction, prompting companies to establish a sound ESG information disclosure system. Thirdly, it provides crucial evidence for ESG investors, compelling corporate managers to pay more attention to the impact of ESG management principles on the company and consider the company's future sustainable development.